2022
DOI: 10.1292/jvms.22-0047
|View full text |Cite
|
Sign up to set email alerts
|

<i>Campylobacter</i> spp. prevalence and fluoroquinolone resistance in chicken layer farms

Abstract: Chicken is a major source of human campylobacteriosis. Chicken meat originates not only from broilers but also from spent layers; however, few reports have reported the prevalence and antimicrobial resistance of Campylobacter spp. in layers in Japan. Therefore, we investigated the prevalence and antimicrobial susceptibility of Campylobacter spp. in 47 layer farms in Japan. Fecal samples were collected from the youngest and oldest flocks on the farm, and Campylobacter spp. was isolated from 46/47 (97.9%) farms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Of the nine ST21 isolates obtained in the present study, six (66.7%) were also resistant to these three antimicrobials. Moreover, we reported that the two most abundant STs in C. jejuni isolated from Japanese layer flocks are ST4389 (eight isolates) and ST6704 (seven isolates), and 93.3% (14/15) of them are ampicillin-resistant [ 32 ]. In that study, two ST354 and two ST918 isolates were obtained from layer flocks, of which 75.0% (3/4) were susceptible to all the tested antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine ST21 isolates obtained in the present study, six (66.7%) were also resistant to these three antimicrobials. Moreover, we reported that the two most abundant STs in C. jejuni isolated from Japanese layer flocks are ST4389 (eight isolates) and ST6704 (seven isolates), and 93.3% (14/15) of them are ampicillin-resistant [ 32 ]. In that study, two ST354 and two ST918 isolates were obtained from layer flocks, of which 75.0% (3/4) were susceptible to all the tested antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Asakura et al [ 3 ] reported ST22 as the most prevalent ST in C. jejuni isolated from human campylobacteriosis cases in Osaka Prefecture, Japan, between 2010 and 2011. In contrast, ST22 C. jejuni is less abundant in cattle and poultry [ 2 , 30 , 32 , 33 ]. Thus, humans might exhibit enteritis easily when infected with ST22, compared to that with other STs.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why the incidence of infection can be high in laying hen farms. Infection rates of 70% [ 40 ], 90% [ 41 ], 97.9% [ 42 ] and up to 100% [ 43 ] have been reported in hen flocks from different countries, although lower incidence rates are also reported in the literature [ 38 , 43 , 44 , 45 , 46 , 47 ]. Several factors may influence the incidence of infection in poultry farms, and different fomites such as rodents, wild birds, visitors, equipment, drinking water and flies may carry the germ to flocks [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that Campylobacter prevalence in layer flocks was 84.0%; C. jejuni ST4389 was the most frequent sequence type, and ciprofloxacin resistance was 19.8% [ 33 ]. In this study, we found elevated intra-flock Campylobacter prevalence (80.0%) and mean concentration (5.2 log 10 CFU/g) in cecal contents from Campylobacter -positive flocks at the time of slaughtering.…”
Section: Discussionmentioning
confidence: 99%
“…However, ampicillin is excluded from this ban because the concentration of ampicillin residue in chicken eggs during and after administration does not exceed the maximum allowed (0.01 mg/kg) [ 10 ]. Therefore, ampicillin can be used in layers more easily and safely than other antimicrobials, which in turn may favor the selection of ampicillin-resistant C. jejuni in layer farms [ 33 ].…”
Section: Discussionmentioning
confidence: 99%